The Influence of Think Pair Share (TPS) Cooperative Learning Model on Students' Mathematical Communication Ability In Class VIII SMP Negeri 12 Pematangsiantar - Simanjuntak, Fretty Maria; Sidabutar, Ropinus; Sauduran, Golda Novatrasio (EduMatika: Jurnal MIPA, 2022)
The purpose of this study was to determine the effect of the use of the learning model, the effect of the Think Pair Share (TPS) cooperative learning model on the mathematical communication skills of students in class VIII of SMP Negeri 12 Pematangsiantar. The design of this study used a pretest-posttest only control group design. The population in this study were all students of class VIII SMP Negeri 12 Pematangsiantar T.A 2022/2023, and the sample in this study were all students of class VIII-6 SMP Negeri 12 Pematangsiantar T.A 2022/2023 totaling 30 students. The instruments used in this study are validity, reliability, level of difficulty of test items and distinguishing power of test items. The data obtained were then analyzed using data analysis techniques, the average value of the Think Pair Share (TPS) learning model was 82.13 and the average mathematical communication ability was 56.03. The results of hypothesis testing after obtained thitung = 11.052 and ttable = 2.045. This means that thitung > from ttable which indicates the null hypothesis is rejected. Based on the description, it is concluded that the use of the Think Pair Share (TPS) learning model has an influence on students' mathematical communication skills in learning functions in class VIII of SMP Negeri 12 Pematangsiantar